Genetic contribution of cytoplasmic lineage effect on feed efficiency in Nellore cattle - Grigoletto, L.; Perez, B. C.; Santana, M. H.A.; Baldi, F. [UNESP]; Ferraz, J. B.S. (Elsevier, 2017)
This study estimated the genetic contribution to genetic variance components and genetic parameters from cytoplasmic lineage effects through the transmission of cytoplasmic components, mainly, the mitochondrial genome evaluated from feed efficiency indicators. Records on 1569 Nellore males (castrated and young bulls) and females (heifers) were used for the following traits, dry matter intake (DMI), average daily gain (ADG), feed conversion ratio (FCR), and residual feed intake (RFI). Genetic variances were estimated by the bayesian approach using Gibbs2f90 program in two univariate animal models. General model (Mgen) which included the direct additive genetic variance as the random effect and the cytoplasmic lineage model (Mlc) included besides the direct additive genetic variance also the cytoplasmic lineage as random effects. Direct heritability estimates by Mgen for DMI, ADG, FCR and RFI were 0.42±0.09, 0.37±0.09, 0.17±0.06 and 0.30±0.10, respectively, while, the direct heritability coefficients estimated by Mlc were 0.41±0.09, 0.35±0.09, 0.15±0.06 and 0.27±0.10. The percentage of cytoplasmic lineage as the proportion of total phenotypic variance ranged from 1.1% to 2.1% for the feed efficiency traits. However, this percentage increase to 14.5% for RFI, if the cytoplasmic effect was take into account as proportion of the additive genetic variance. These results indicate that genetic improvement in feed efficiency can be achieved through selection and the traits analyzed showed enough genetic variability, thus the inclusion of feed efficiency in animal breeding programs of Nellore cattle is feasible. The inclusion of cytoplasmic lineage effect to evaluate feed efficiency indicator traits has not produced substantial gains to the genetic evaluation, as it does not improve the prediction ability of the models by deviance information criteria for Bayesian models. However, on a long-term basis, the identification of the best cytoplasmic lineages in the population may help to assure continuous improvement for the traits of interest.
Keywords: Bayesian models; Beef cattle; Cytoplasmic effect; Feed efficiency; Heritability